Help-Seeking Behavior Levels among UNNES Guidance and Counseling Students Reviewed from Gender Perspective - Naufalia, Salisi; Sugiharto, Dwi Yuwono Puji; Ahmadi, Farid (Study Program of Guidance and Counselling, Post Graduate Program, Universitas Negeri Semarang, 2024)
Students' mental health problems are frequently triggered by the demanding adjustmalest to college life. This study aimst to examine the students' tendency to seek a professional help and identifies the gender differences in this behavior. The sample involves 232 undergraduate students from Guidance and Counseling departmalest at Universitas Negeri Semarang. The data analysis of this study reveals that there are no appreciable variations in the tendency of male and female students to seek a professional help when they recognize the need for counseling. However, the level of confidence that the two genders have in mental health professionals differs significantly. Interestingly, the different Guidance and Counseling students, who are expected to learn about counseling, have different perceptions on how much they can trust mental health practitioners.